Optimizing Poverty Alleviation in Indonesia: The Impact of Islamic Microfinance on Farmer Communities - A. A. Mahfudz; R. A. Ahmad; H. Maulana (Экономика: стратегия и практика, 2024)
The emergence of Islamic microfinance in Indonesia has become an urgent necessity to provide financing for people experiencing poverty in rural areas. Providing interest-free funding is a solution to help people experiencing poverty improve their income through Islamic philanthropic funds such as zakat, infaq, and sadaqah. This study aims to show the Islamic microfinance model that can be applied by villages in Indonesia and utilize the village’s potential as a model for Islamic microfinance to alleviate poverty. This research undertakes quantitative research by employing SEM (Structural Equation Model) analysis with the Lisrel 8.80 tool. The results of this study found that Islamic microfinance models such as zakat and infaq significantly improve the quality of life of communities through the provision of goods and interest-free loans. Specifically, the analysis revealed that zakat and infaq contributions positively affected community income, with a t-value of 2.54 and 2.74, respectively, indicating significant statistical influence. However, it was found that sadaqah contributions have a lower influence on community income because the programs funded through this source occur only once a year, prompting communities to seek other sources of loans for their needs. This study implies that Islamic philanthropy institutions provide the best solution to empower farmers’ communities with new models and strategies. The novelty of this study is the Islamic microfinance model through optimizing Islamic social funds to alleviate poverty. Different research methodology using a quantitative approach is recommended for future research to enrich the literature in this field.